Systemic immune-inflammation index is associated with coronary heart disease: a cross-sectional study of NHANES 2009–2018 - Ma, Jiwen; Li, Ka (Frontiers in Cardiovascular Medicine, 2023)
Abstract: (1)Background: Inflammation has been linked to the development of coronary heart disease (CHD). The systemic immune inflammation index (SII) is a useful biomarker of systemic inflammation. Our study aimed to explore the correlation between SII and CHD.(2)Methods: We conducted a multivariate logistic regression analysis, smoothing curve fitting, and segmented model comparison on 15,905 participants with a CHD prevalence of 3.31% and a mean age of 46.97 years. (3)Results: Adjusting for gender, age, and race, we found a negative association between SII and CHD [odds ratio (OR) 0.66; 95% confidence interval (CI) 0.48, 0.90]. There was an inverse trend where increasing SII was associated with decreasing odds of CHD (p for trend=0.0017). After further adjustment, the association was strengthened, with a similar trend (p for trend=0.0639). Smoothing curve fitting demonstrated a gender-specific association between SII and CHD.(4)Conclusions: Our findings suggest that higher SII values may be associated with a higher incidence of CHD, which varies by gender. SII may be a cost-effective and convenient method to detect CHD. Further studies are needed to confirm the causality of these findings in a larger prospective cohort.